Analisis Kausalitas antara Kualitas Produk, Kualitas Pelayanan, dan Loyalitas Pelanggan di PT. FIFGROUP - Qowiyah Al Zahro, Yayang Qowiyah Al Zahro; Nurfida, Anita; Fatoni, Fatoni (JURMATIS (Jurnal Manajemen Teknologi dan Teknik Industri), 2024)
In the digital era, FIFGROUP must meet customer expectations with fast service. This study analyzes the impact of service complaints on customer loyalty using Smart PLS and Fishbone Diagram for identifying key factors. The research employs a quantitative design with a survey approach to assess the impact of product and service quality on Spektra customer loyalty at FIFGROUP. Utilizing a sample of 100 respondents from Kranggan Cibubur, the study gathers in-depth data through questionnaires and observations. The research procedure involves a two-way model to analyze variable relationships, validity, reliability, and mediation effects, with Fishbone Diagram for identifying and prioritizing main problem causes at FIFGROUP. Improvement in product quality (coefficient 0.261; T-statistic 2.902) and service (coefficient 0.206; T-statistic 2.070) at Spektra FIFGROUP significantly enhances customer loyalty. Resource optimization and service digitalization are crucial for long-term effectiveness.